1992
DOI: 10.1542/peds.89.3.454
|View full text |Cite
|
Sign up to set email alerts
|

Infant Health and Development Program for Low Birth Weight, Premature Infants: Program Elements, Family Participation, and Child Intelligence

Abstract: The Infant Health and Development Program was an eight-site randomized controlled trial testing the efficacy of early intervention to enhance the cognitive, behavioral, and health status of low birth weight, premature infants. The 377 intervention families received for the first 3 years of life: (1) pediatric follow-up, (2) home visits, (3) parent support groups, and (4) a systematic educational program provided in specialized child development centers. The control group (n = 608) received the same pediatric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 236 publications
(32 citation statements)
references
References 0 publications
0
31
1
Order By: Relevance
“…On the other hand, it is striking how few hours of early childhood education were offered to children in Even Start families when compared with the hours offered to children who participated in some other programs that have generated large effects on child outcomes. Even Start projects offer only 20% to 25% of the amount of service offered to children in the Abecedarian, Carolina Approach to Responsive Education, and Infant Health and Development Program projects (Ramey et al, 1992; Ramey & Campbell, 1988; Wasik, Ramey, Bryant, & Sparling, 1990). Each of these projects provided full-day care (2000 or more hours a year), used a common curriculum in all sites, and had large positive short-term effects of between 10 and 15 points (0.7 SD to 1.0 SD ) on standardized IQ tests.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it is striking how few hours of early childhood education were offered to children in Even Start families when compared with the hours offered to children who participated in some other programs that have generated large effects on child outcomes. Even Start projects offer only 20% to 25% of the amount of service offered to children in the Abecedarian, Carolina Approach to Responsive Education, and Infant Health and Development Program projects (Ramey et al, 1992; Ramey & Campbell, 1988; Wasik, Ramey, Bryant, & Sparling, 1990). Each of these projects provided full-day care (2000 or more hours a year), used a common curriculum in all sites, and had large positive short-term effects of between 10 and 15 points (0.7 SD to 1.0 SD ) on standardized IQ tests.…”
Section: Discussionmentioning
confidence: 99%
“…Gender of child was evenly split, with 50% girls. In the sample of 493 used in the analyses, 57% educational child-care program at a child development center in the 2nd and 3rd years, and bimonthly parent group meetings in the child's 2nd and 3rd years (Ramey et al, 1992). of mothers were African American and 43% were White.…”
Section: Methodsmentioning
confidence: 99%
“…The Early Head Start evaluation, for example, found that parenting and social-emotional developmental outcomes were strongest for Black children and that families experiencing three risk factors (e.g., single parenthood, receiving public assistance, teen parenthood) showed stronger effects than families with either fewer or more risk factors (Love et al, 2002). Within the early intervention literature, stronger results have also been reported for more intensive programs measured as hours of contact, part-day versus full-day, total years of intervention, and extent of compliance with program standards (Campbell & Carmey, 1994;DeSiato, 2004;Love et al, 2002;Ramey et al, 1992;Reynolds et al, 2001). For these reasons, we examined differential pre-K effects by family income (using free lunch eligibility as a proxy for family income) and racial-ethnic group of the children and by their enrollment in half-or full-day programs.…”
Section: Available Research On Pre-k Programsmentioning
confidence: 99%